Legal Protection for Contractors Against Unilateral Termination by the Employer under Construction Contracts - Moh. Choiru Syahil; Samian Samian; Sarwono Hardjomuljadi (Interdisciplinary Social Studies, 2025)
This study examines legal protection for service providers against unilateral contract termination by service users in the construction sector in Indonesia. This problem arises from the imbalance in the legal and economic positions between the parties, as well as weak legal regulations that provide room for broad interpretation for service users. This study uses a normative juridical method with a statutory, conceptual, case, and comparative legal approach. The analysis was conducted on the Civil Code (KUHPerdata), Law Number 2 of 2017 concerning Construction Services, and Presidential Regulation Number 16 of 2018, then compared with the legal systems of the European Union, China, and South Korea. The results of the study indicate that legal protection in Indonesia is still administrative and formalistic, not guaranteeing proportional contractual justice for service providers. Therefore, this study recommends a balanced contractual protection model, which emphasizes compensation obligations, the principle of good faith, and the establishment of an independent contract mediation institution as a solution towards a fair, transparent, and sustainable contractual legal system.